Massive complicated secondary inguinal mycetoma: a case series. (20th January 2021) - Ezaldeen, Eshraga Abakar; Ahmed, Eiman Siddig; Fahal, Ahmed Hassan
Abstract: Mycetoma is a chronic subcutaneous granulomatous disease of the soft tissue and extremities. Herein we report four cases of mycetoma caused by different agents, two caused by Madurella mycetomatis, with Actinomadura madurae and Streptomyces somaliensis affecting the others. These lesions originated at different sites but eventually spread to the inguinal region. The exact mechanism for such spread is still unknown and the clinical presentation of our case series was distinctive and required intensive follow-up for appropriate management.